Community empowerment in preventing dental caries through education and routine examinations: Pemberdayaan masyarakat dalam pencegahan karies gigi melalui edukasi dan pemeriksaan rutin - Wulan, Komang Rhismala Oktaryanti; Byba Melda Suhita; I Gusti Putu Dado Armawan (KHD Production, 2026)
Community empowerment in preventing dental caries is a relevant and strategic approach to improving public oral health. This community service program aimed to enhance community knowledge and promote preventive behaviors through educational interventions and routine dental examinations at a clinic. The implementation method was designed to effectively achieve empowerment and prevention goals by integrating health education with direct health services. Evaluation results demonstrated a significant improvement in participants’ understanding following the intervention. Prior to the educational session, only 40% of participants correctly answered questions and demonstrated adequate knowledge of basic dental caries prevention. This proportion increased to 85% after the intervention, indicating the effectiveness of the educational approach. Clinical examinations of 50 participants revealed that 18 individuals (36%) had dental caries, with varying severity. The program also demonstrated strong community engagement, as evidenced by active participation and positive responses throughout the activities. The findings suggest that community empowerment through education and routine dental checkups is effective in increasing knowledge, fostering behavioral change, and raising awareness of the importance of maintaining sustainable oral health.